Avaliação da compactação da cromatina espermática durante o trânsito do espermatozoide através do epidídimo de camundongos - Martins, Alexsandra Alves Bezerra (2019)
Several studies have shown that during the passage of the spermatozoid through the epididymis, the spermatic chromatin undergoes the formation of disulfide bridges between the protamines increasing the condensation of the genetic material, a fundamental step for the protection and maintenance of DNA stability. The present study aims to evaluate the process of sperm condensation of chromatin during spermatozoid maturation in the epididymis of mice. For this, spermatozoa were collected from the head, body and tail regions of the epididymis of six mice. These spermatozoa were evaluated by computational image analysis of smears stained with toluidine blue, analyzing the spatial distribution of the condensation of chromatin process and, the mean decondensation and heterogeneity of the sperm heads. Spermatozoa were also evaluated by transmission electron microscopy (TEM), and four levels of non-condensation were defined. The proportion of spermatozoa with high chromatin (mature) condensation was lower in the head when compared to the other epididymal regions, in both methodologies used. In addition, low condensation levels in the basal half (LBH) and the entire length of the head (LCT) were prevalent in this region. In the body, there was a predominance of low condensation of the base (LB) and in the central region (LCR). In the tail, all levels of low condensation decreased considerably, being practically non-existent, except in the central region (LCR), which still were prevailed in small numbers. Based on these data, a sequence of the condensation process in the murine spermatozoa was proposed. The condensation would start at the apical region towards the base and from the lateral sides to the center of the spermatozoa's head, and compaction process would finish near the base. Subsequently, the compaction would occur in the direction of the insertion of the tail (base) to the center and finally, in the central region of the head. The analysis of the means of decondensation and heterogeneity of the chromatin made by image analysis of TB stained smears and the ones which were performed by TEM demonstrated that the process of chromatin compression of mice spermatozoa started during spermiogenesis continues during transit in the epididymis.